2014
DOI: 10.11646/zootaxa.3780.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Descriptions of three new species of Marcusenius Gill, 1862 <br />(Teleostei: Mormyridae) from South Africa and Mozambique

Abstract: Morphological and genetic studies of mormyrid fishes belonging to the genus Marcusenius from South Africa and Mozambique revealed four species of which three are described as new. Marcusenius pongolensis is widespread throughout the Incomati, Pongola and Kosi river systems, and sparsely represented in the Limpopo River system in South Africa. Marcusenius krameri sp. nov. is endemic to the Limpopo River system, and is the sister taxon of M. caudisquamatus sp. nov. from the Nseleni and Mhlatuze river systems in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 47 publications
5
32
1
Order By: Relevance
“…Furthermore, M. krameri's EOD waveform was supported as an entity distinctly separate from the EODs of all other South African bulldog fish species in comparisons of the two sexes. This is in agreement with Maake's et al (2014) morpho-genetic study that designated species status for M. krameri. Maake et al (2014) also reported intraspecific morphological differentiation in M. pongolensis: specimens from the independent Kosi System clustered separately from the other South African pongolensis origins, because of significant differences in five morphological characters (Maake et al 2014: Figure 5b, Table 4).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, M. krameri's EOD waveform was supported as an entity distinctly separate from the EODs of all other South African bulldog fish species in comparisons of the two sexes. This is in agreement with Maake's et al (2014) morpho-genetic study that designated species status for M. krameri. Maake et al (2014) also reported intraspecific morphological differentiation in M. pongolensis: specimens from the independent Kosi System clustered separately from the other South African pongolensis origins, because of significant differences in five morphological characters (Maake et al 2014: Figure 5b, Table 4).…”
Section: Discussionsupporting
confidence: 91%
“…We studied four geographical samples of M. pongolensis, as re-described by Maake et al (2014). The sample from the Sabie River (35 females, 10 males) matched the one from the Kosi System (13 females, 8 males) in showing statistically significant sex differences in each one of the six EOD characters studied (ANOVA, p< 0.02).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations